Environmental and societal factors associated with COVID-19-related death in people with rheumatic disease: an observational study. (September 2022) - Izadi, Zara; Gianfrancesco, Milena A; Schmajuk, Gabriela; Jacobsohn, Lindsay; Katz, Patricia; Rush, Stephanie; Ja, Clairissa; Taylor, Tiffany; Shidara, Kie; Danila, Maria I; Wysham, Katherine D; Strangfeld, Anja; et al.
Summary: Background: Differences in the distribution of individual-level clinical risk factors across regions do not fully explain the observed global disparities in COVID-19 outcomes. We aimed to investigate the associations between environmental and societal factors and country-level variations in mortality attributed to COVID-19 among people with rheumatic disease globally. Methods: In this observational study, we derived individual-level data on adults (aged 18–99 years) with rheumatic disease and a confirmed status of their highest COVID-19 severity level from the COVID-19 Global Rheumatology Alliance (GRA) registry, collected between March 12, 2020, and Aug 27, 2021. Environmental and societal factors were obtained from publicly available sources. The primary endpoint was mortality attributed to COVID-19. We used a multivariable logistic regression to evaluate independent associations between environmental and societal factors and death, after controlling for individual-level risk factors. We used a series of nested mixed-effects models to establish whether environmental and societal factors sufficiently explained country-level variations in death. Findings: 14 044 patients from 23 countries were included in the analyses. 10 178 (72·5%) individuals were female and 3866 (27·5%) were male, with a mean age of 54·4 years (SD 15·6). Air pollution (odds ratio 1·10 per 10 μg/m 3 [95% CI 1·01–1·17]; p=0·0105), proportion of the population aged 65 years or older (1·19 per 1% increase [1·10–1·30]; p<0·0001), and population mobility (1·03 per 1% increase in number of visits to grocery and pharmacy stores [1·02–1·05]; p<0·0001 and 1·02 per 1% increase in number of visits to workplaces [1·00–1·03]; p=0·032) were independently associated with higher odds of mortality. Number of hospital beds (0·94 per 1-unit increase per 1000 people [0·88–1·00]; p=0·046), human development index (0·65 per 0·1-unit increase [0·44–0·96]; p=0·032), government response stringency (0·83 per 10-unit increase in containment index [0·74–0·93]; p=0·0018), as well as follow-up time (0·78 per month [0·69–0·88]; p<0·0001) were independently associated with lower odds of mortality. These factors sufficiently explained country-level variations in death attributable to COVID-19 (intraclass correlation coefficient 1·2% [0·1–9·5]; p=0·14). Interpretation: Our findings highlight the importance of environmental and societal factors as potential explanations of the observed regional disparities in COVID-19 outcomes among people with rheumatic disease and lay foundation for a new research agenda to address these disparities. Funding: American College of Rheumatology and European Alliance of Associations for Rheumatology.